Non-pharmacological interventions for bone health after stroke: a systematic review - Sallehuddin, Hakimah; Ong, Terence; Md. Said, Salmiah; Ahmad Tarmizi, Noor Azleen; Loh, Siew Ping; Wan, Chieh Lim; Nadarajah, Reena; Lim, Hong Tak; Mohd Zambri, Nurul Huda; Mohd Zambri, Nurul Huda; Shariff Ghazali, Sazlina (Public Library of Science, 2022)
Objective: To examine the effectiveness and safety of non-pharmacological interventions to reduce bone loss among post-stroke adult patients. Data sources: Cochrane Central Register of Controlled Trials (CENTRAL), Cochrane Database for Systematic Reviews, MEDLINE, CINAHL, ScienceDirect, Scopus, PubMed and PeDRO databases were searched from inception up to 31st August 2021. Methods: A systematic review of randomized controlled trials, experimental studies without randomization and prospective cohort studies with concurrent control of non-pharmacological interventions for adult stroke patients compared with placebo or other stroke care. The review outcomes were bone loss, fall and fracture. The Cochrane Risk of Bias Tools were used to assess methodological quality, and Grading of Recommendations, Assessment, Development and Evaluations Framework to assess outcome quality. Synthesis Without Meta-Analysis (SWiM) was used for result synthesis. Results: Seven studies (n = 453) were included. The methodological and outcome qualities varied from low to moderate. There were statistically significant changes between the intervention and parallel/placebo group in bone mineral density, bone mineral content, cortical thickness and bone turnover markers with specific physical and vibration therapies (p<0.05). Falls were higher in the intervention group, but no fracture was reported. Conclusion: There was low to moderate evidence that physical and vibration therapies significantly reduced bone loss in post-stroke patients at the expense of a higher falls rate. The sample size was small, and the interventions were highly heterogeneous with different duration, intensities and frequencies. Despite osteoporosis occurring with ageing and accelerated by stroke, there were no studies on vitamin D or protein supplementation to curb the ongoing loss. Effective, high-quality non-pharmacological intervention to improve post-stroke bone health is required.